Sejarah Evolusi Sunnah - Sahid HM Sahid HM (AL-TAHRIR, 2011)
This study tries to analyze Fazlur Rahman’s thought on the historical evolution of the sunnah as his response to some orientalists when he was in the West and to muslem scholars who had blamed him when he was in Pakistan. In fact, the study of Prophetic Sunnah applied by orientalists came up with conclution that the `sunnah is not original from the Prophet period. It is so since muslim scholars in Indo-Pakistan contradiction and are not in line with Rahman’s views of sunnah. In critizing the orientalists’s views of Prophetic Sunnah, Rahman tried to elaborate the historical contect of sunnah. According to him, the false views of orientalists were naturally caused by their overlapping perception of sunnah as the living practice and the concept of normative. For muslim scholars, Rahman realized the numerous thoughts among them. Rahman pointed out that evolution of sunnah was historically valid and originally sourced from Muhammad. It is the source of Islamic law. Rahman also said that sunnah is a living tradition of prophet’s Muhammad and a general umbrella concept.